(untitled) (International Journal of Physiotherapy, 2020)
Background: It is essential to find out the presence of shin splint in recreational marathon runners to prevent the injury from causing more damage. This study was conducted to identify shin splint in recreational marathon runners in Krishna Hospital, Karad. This study was designed to provide meaningful insight into the cause of shin splint in recreational marathon runners. Objectives of the study were to find out the impact of shin splint in recreational marathon runners and to assess the severity of shin splint in recreational marathon runners of age group 20-30 years both males and females in Krishna Hospital, Karad. Material and Methods: 190 recreational marathon runners who fit in the criteria were given Runner’s Questionnaire and were asked to fill it. Result: There was marked significance pain was present during(p=0.04) and running throughout(p<0.0001) in recreational marathon runners. Conclusion: It was concluded from the present study that there is a prevalence of shin splint in marathon runners. Shin splint was found more in females (55.3%)than in males (44.7%). Based on the duration of pain and shoe surface was found to be more prevalent to cause shin splint in marathon runners.